2003
DOI: 10.1046/j.1439-0531.2003.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osteopontin (OPN) mRNA in Bovine Ovarian Follicles and Corpora Lutea

Abstract: The matricellular protein osteopontin (OPN) plays a role in various physiological processes, including angiogenesis and tissue remodelling. As these processes are essential for the maintenance of ovarian physiology, the aim of the study was to investigate the expression of OPN (mRNA) in ovarian cells and to evaluate whether it can be regulated by gonadotrophins. Using conventional RT-PCR and real-time PCR, we have detected and quantified OPN mRNA as well as glyceraldehyde-3-phosphate dehydrogenase (GAPDH) mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The comparison of fish OP‐L protein with mammalian osteopontin expression patterns indicates that both proteins may play a similar role in calcified tissues and gonads, for example in bone remodeling by mediating osteoclast attachment to the mineralized bone matrix during resorption [23,34–36] and/or in matrix mineralization by regulating calcium phosphate crystal deposition [26,37–39], and in gonads by preventing calcium‐containing‐crystal aggregation[40,41]. The restricted tissue distribution of the OP‐L gene transcript also indicates that fish protein may be less pleiotropic than that from mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of fish OP‐L protein with mammalian osteopontin expression patterns indicates that both proteins may play a similar role in calcified tissues and gonads, for example in bone remodeling by mediating osteoclast attachment to the mineralized bone matrix during resorption [23,34–36] and/or in matrix mineralization by regulating calcium phosphate crystal deposition [26,37–39], and in gonads by preventing calcium‐containing‐crystal aggregation[40,41]. The restricted tissue distribution of the OP‐L gene transcript also indicates that fish protein may be less pleiotropic than that from mammals.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out the fact that differences in gene expression in soft tissues could be related to different developmental or physiological stages of the specimens used in both studies, as evidenced by the regulation of OP-L gene expression in brook trout ovary during ovulation [19]. The comparison of fish OP-L protein with mammalian osteopontin expression patterns indicates that both proteins may play a similar role in calcified tissues and gonads, for example in bone remodeling by mediating osteoclast attachment to the mineralized bone matrix during resorption [23,[34][35][36] and ⁄ or in matrix mineralization by regulating calcium phosphate crystal deposition [26,[37][38][39], and in gonads by preventing calcium-containing-crystal aggregation 26 [40,41]. The restricted tissue distribution of the OP-L gene transcript also indicates that fish protein may be less pleiotropic than that from mammals.…”
Section: Op-l Protein Plays a Role In The Process Of Mineralizationmentioning
confidence: 99%
“…To select a stable reference or housekeeper gene, analysis of putative reference genes was carried out using the geNorm version 3.4 Excel (Microsoft, Redmond, WA) add-in (99). In this study, housekeeping genes analyzed included those for ␤-actin (4), ubiquitin (67), glyceraldehyde phosphate dehydrogenase (14), 18S ribosomal RNA (24), and peptidylprolyl isomerase A (74). The gene stability measure M that geNorm determines is defined as the average pairwise variation V of a particular gene with all other potential reference genes (99).…”
Section: Real-time Quantitative Reverse Transcription Pcrmentioning
confidence: 99%
“…Furthermore, a novel ovarian protein, sharing sequence similarity with mammalian and chicken OPNs, was detected in trout periovulatory ovary (Bobe & Goetz 2001). OPN transcripts were also detected in bovine ovarian follicles and corpus lutea (Brunswig-Spickenheier & Mukhopadhyay 2003). Recently, results of a detailed study have indicated that OPN is localized in bovine luteal cells during the luteal phase of the estrous cycle and is involved in the development and regression of the corpus luteum (Poole et al 2013).…”
Section: Introductionmentioning
confidence: 99%